Optimal management of older people with frailty non-weight bearing after lower limb fracture: a scoping review. (17th May 2021) - Aloraibi, Saleh; Booth, Vicky; Robinson, Katie; Lunt, Eleanor Katharine; Godfrey, Deborah; Caswell, Alan; Kerr, Margaret; Ollivere, Benjamin; Gordon, Adam Lee; Gladman, J R F
Abstract: Background: Patients with lower limb fractures who are non-weight bearing are at risk of the complications of the associated immobility and disability, particularly people with frailty, but there is lack of clarity about what constitutes optimal care for such patients. A scoping literature review was conducted to explore what evidence is available for the management of this patient group. Methods: MEDLINE (PubMed) CINAHL, EMBASE and the Cochrane databases of published literature and the HMIC and SIGLE sites for grey literature were searched for primary research studies and expert reports, using an iterative approach initially including the key term 'non-weight bearing'. All study types were included. Analysis was by narrative synthesis. Results: No papers were identified from a search using the key phrase 'non-weight bearing'. With this term removed, 11 indirectly relevant articles on lower limb fractures were retrieved from the searches of the electronic databases comprising three observational studies, five non-systematic review articles, a systematic review, an opinion piece and a survey of expert opinion that had relevance to restricted weight bearing patients. The observational studies indicated depression, cognition and nutrition affect outcome and hence have indirect relevance to management. The non-systematic reviews articles emphasised the importance of maintaining strength and range of movement during immobilisation and advised an orthogeriatric model of care. Fourteen UK and 97 non-UK guidelines relevant to fragility fractures, falls and osteoporosis management were found in the grey literature, but none made specific recommendations regarding the management of any period of non-weight bearing. Discussion: These findings provide a summary of the evidence base that can be used in the development of a clinical guideline for these patients but is not sufficient. We propose that, a guideline should be developed for these patients using an expert consensus process.